Tsetse and trypanosomosis associated socio-economics and environmental variables limiting livestock and dairy development in northern parts of Edo State, Nigeria - Osue, Hudu O; Ibrahim, Mariam; Suru, Mohammad I; Haruna, Mohammed K; Omaga, Moses; Oshionei, Aisha; Abdulkareem, Nura; Umar, Dora A (International Journal of Natural Sciences Research, 2023)
Edo North is in a low-lying plain with hilly terrain rising up to 672 meters above sea level in some area. It has good vegetation cover, forest reserves, network of perennial rivers and streams and favourable eco-climatic conditions ideal for tsetse breeding. Both primary and secondary socioeconomics, environmental and ecological-health derived data were subjected to descriptive and percentage statistical analyses. Interactive meetings were held with key informants (n=38); Local Government officials, community leaders and representatives of Fulani pan sociocultural group in Edo North were interviewed and administered questionnaire. Focus group discussions were held with herders (n=85) and natives (n=350) who freely participated. The huge livestock and dairy production potential of the study area are due to availability of natural forage, crop fodders, agro-based byproducts, and water all year round. Most herders (80%) and natives (60%) have good knowledge of the disease and vector, but only a few (10%) knows the mechanism of transmission. Prevailing mistrust and widespread apprehension over herders-farmers’ clashes and other criminalities were attributed to itinerant nomadic Fulani by majority opinions. Lack of access to grazing lands, perceived poor rate of returns using planted fodder and feed concentrates were viewed as uneconomic compared to traditional free range grazing. Most pastoralists believed that government support to livestock sub-sector is ridiculously low compared to crop commodities. The dire need to address the thematic areas that can strongly impact on job, wealth creation, means of livelihood, and substantially facilitate economic diversification drive cannot be overemphasized.